Level Aktivitas Fisik dan Perilaku Sedenter Siswa SD di Kota Bandung: Penelitian Survei - Ismiyani Nurlatifah; Ricky Wibowo; Wildan Alfia Nugroho (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to describe the level of physical activity and sedentary behavior among elementary school students in Bandung City. The study employed a quantitative approach with a descriptive survey design. The sample consisted of 117 elementary school students selected using cluster sampling with a purposive approach. Physical activity was measured using the Physical Activity Questionnaire for Children (PAQ-C), while sedentary behavior was assessed using the Adolescent Sedentary Activity Questionnaire (ASAQ). In addition, nutritional status was identified using the Body Mass Index-for-Age (BMI-for-Age) indicator based on the WHO Growth Reference 5–19 Years. Data were analyzed descriptively using mean, standard deviation, frequency, and percentage. The results showed that students' physical activity level was categorized as moderate, with a mean PAQ-C score of 2.91. The average sedentary behavior duration was 688.74 minutes per day, or approximately 11.48 hours per day. The most dominant sedentary activity was watching television or using a mobile phone (1,349.02 minutes/week), followed by sitting and chatting (566.58 minutes/week) and using a computer or laptop for entertainment (556.99 minutes/week). Based on BMI-for-Age nutritional status, most students were classified as having normal nutritional status (61.5%), although overweight (22.2%) and obesity (8.5%) were still observed. Male students demonstrated higher physical activity levels than female students, whereas female students and 12-year-old students exhibited higher sedentary behavior durations. This study concludes that elementary school students in Bandung City have a moderate level of physical activity but are accompanied by high sedentary behavior and a considerable proportion of students with excess nutritional status. Therefore, efforts to improve children's health should focus not only on increasing physical activity but also on reducing sedentary behavior to support optimal health and nutritional status among school-aged children. Keywords: Physical Activity, Sedentary Behavior, Nutritional Status, BMI-For-Age, Elementary School Students